Evaluation of selected fungicides for the management of white rust of Indian mustard: EVALUATION OF FUNGICIDES FOR THE MANAGEMENT OF WHITE RUST OF INDIAN MUSTARD - K BASAVARAJ; A S RATHI; N P GURAV; RAKESH PUNIA; ANIL KUMAR (Journal of Oilseeds Research, 2020)
Field studies were conducted to evaluate the efficacy ofselected fungitoxicants viz., mancozeb 75 WP @ 0.2%, metalaxyl 8%+ mancozeb 64% @ 0.2%, hexaconazole 5 EC @ 0.05%, cymoxanil 8% + mancozeb 64% @ 0.1% and azoxystrobin 23% SC 0.05% as a single spray treatment at 45 DAS and each four fungicides at 60 DAS in succession of mancozeb 75 WP at 45 DAS in control of white rust disease. The experiment was carried out for two consecutive years during rabi 2014-15 and 2015-16 with susceptible Indian mustard cultivar Varuna. All the fungicides tested were significantly effective in reducing the disease over the check; however the level of efficacy varied among the treatments. The plots sprayed with mancozeb (0.2%) at 45 DAS followed by azoxystrobin (0.05%) at 60 DAS recorded significantly lower disease severity over the other treatments both at leaf and staghead phase with significant highest seed yield of 1906.81 kg/ha which was 42.33% higher over the check. The spray of mancozeb (0.2%) at 45 DAS followed by metalaxyl + mancozeb (0.2%) at 60 DAS was the next best treatment among combinations of two fungicidal sprays. Among single fungicidal spray treatments, spray of metalaxyl + mancozeb @ 0.2% was effective in reducing white rust at leaf and staghead phases with concomitant increase in seed yield. In general, none of the single spray treatments was found superior over the plots that received two fungicidal sprays i.e. mancozeb at 45 DAS followed by other fungicides at 60 DAS.